Tunneling transport in Ferromagnet/Insulator/Ferromagnet junctions - Freyss, M; P. Mavropoulos; N. Papanikolaou; Bellini, V; R. Zeller; P.H. Dederichs (PHASE TRANSITIONS, 2002)
We study the spin-dependent transport in expitaxial Ferromagnet/Insulator/Ferromagnet junctions. Firstly we show that the tunneling through the insulator can be described by the complex band structure of the insulator in the gap region, i.e. by the metal-induced gap states. Since the imaginary part of the Bloch vector describes the decay of the wave function, we calculate the spectrum of the decay parameters K for several semiconductors. For large thicknesses the state with the smallest K-value dominates the current. In the second part we present the results of ground state calculation for Fe/ZnSe/Fe(001) and related junctions. We obtain a rather localized charge transfer from the interface Fe layer to the neighbouring semiconductor layer, which is largest for the low-valent termination. Moreover we find that the local moments at the interface depend sensitively on the lattice parameter chosen. Finally, we show that in the minority band at E(F) an Fe interface state exists, which deeply penetrates into the barrier.